Anderson-Fabry Disease in Children - Sestito, Simona; Ceravolo, Ferdinando; Concolino, Daniela (Current Pharmaceutical Design, 2013)
Although clinical evidence of major organ damage is typical of adulthood, many of the signs and symptoms of Anderson Fabry Disease (AFD) occur frequently in childhood. The clinical phenotype of AFD in pediatric patients has been described in several studies which show a higher incidence and an earlier onset of symptoms in male patients than in females. These include neurological manifestations (acroparaesthesias, chronic neuropathic pain, hypo-anhidrosis, tinnitus, hearing, loss), gastrointestinal (GI) symptoms (abdominal pain and diarrhea), angiokeratomas, ocular abnormalities (cornea verticillata, tortuous retinal vessels and subcapsular cataracts). Such manifestations may impair quality of life and, because of their unspecific nature, rarely lead to an early diagnosis. In addition, signs of major organ damage (microalbuminuria or proteinuria, urinary hyperfiltration, impaired heart rate variability, left ventricular hypertrophy, stroke) are encountered in children with AFD. Clinical trials of enzyme replacement therapy (ERT) with agalsidase alfa and agalsidase beta have been conducted in children, with clinical and pharmacodinamc effects proved by both enzyme formulations, whereas differences in safety profile and administration were found. Although several studies suggest that ERT should be started before irreversible damage in critical organs have occurred, the issue of when to initiate it has not yet been resolved. More controlled trials must be done in order to demonstrate that an early start of ERT could prevent adult complications and to assess the optimal timing of treatment in children with AFD. This review aims to provide an update of the current understanding for a better approach of pediatric AFD.
Keywords: enzyme replacement therapy